Effects of sex and joint action on voluntary activation - Ema,Ryoichi; Suzuki,Momoka; Kawaguchi,Emi; Saito,Itaru; Akagi,Ryota (PeerJ, 2018)
The current study tested the hypothesis that voluntary activation during maximal voluntary contraction (MVC) conditionally depends on sex and joint action. Twenty-eight healthy adults (14 of each sex) performed knee extensor MVC and plantar flexor MVC at extended and flexed knee positions. Voluntary activation during MVC was assessed using a twitch interpolation technique. The voluntary activation during plantar flexor MVC at the extended knee position was significantly lower (P = 0.020, 95% confidence interval 1.4 to 14.6, Cohen’s d for between-subject design = 0.94) in women (88.3% ± 10.0%) than in men (96.2% ± 6.6%). In contrast, no significant sex differences were shown in the voluntary activation during knee extensor MVC (93.7% ± 5.9% (women) vs. 95.0%  ± 3.9% (men)) and during plantar flexor MVC at the flexed knee position (90.4% ± 12.2% (women) vs. 96.8% ± 5.6% (men)). The voluntary activation during knee extensor MVC was significantly higher (P = 0.001, 95% confidence interval 2.1 to 8.8, Cohen’s d for within-subject design = 0.69) than that during plantar flexor MVC at the extended knee position in women, whereas the corresponding difference was not observed in men. The results revealed that the existence of sex difference in the voluntary activation during MVC depends on joint action and joint angle.
Keywords: Knee extension; Plantar flexion; Sex difference; Twitch interpolation technique